The Use of Muna Language Among Students at English Department of Halu Oleo University - Emisrawati, Emisrawati; Tambunan, Tambunan; Fatmawati, Wa Ode (Journal of Teaching of English, 2021)
This research discusses the use of the Muna language among students at English Department of Halu Oleo University. Language contact that occurs between the students who are from several regencies and tribes became an interesting thing to see how they keep and use their local language. This study focus on How is the use of Muna language among the students who are from Raha city and what is the prospect of Muna language in the community of students in the globalization era. The main data was taken in English department environment, faculty of teacher training and education, Halu Oleo University. Observation and interviews were used by the Researcher in collecting the data in this area. The result of this research shows that the students are no longer use Muna language correctly and properly. It appears that there is a language shift from Muna to Indonesian which began when they live in Raha and continues when they move to Kendari to college. It shows the prospect of Muna language among students is very threatened.